Strong f-f excitation in titanium silicate: Near-UV LED pumped red phosphors with outstanding temperature sensitivity. Issue 19 (1st October 2021) - Ding, Jianyan; Gao, Yanling; Tang, Xueping; Zhou, Jiangcong; Ye, Shanshan; Wu, Dewu; Wu, Quansheng
Abstract: Optical thermometry and white light-emitting diodes (WLEDs) are the research hotspots for Eu 3+ doped phosphors. In this study, a series of Sr2 TiSi2 O8 : Eu 3+ red phosphors were developed in a solid-state reaction method. The luminescent properties of the Sr2 TiSi2 O8 : Eu 3+ phosphor illustrate that Sr2 TiSi2 O8 : Eu 3+ is effectively excited by the NUV LED chip and emit an intense red light with a peak of 618 nm due to the noninversion symmetry coordination of Eu 3+ in Sr2 TiSi2 O8 . The local coordination environment of Eu 3+ was investigated in detail using crystallographic data, spectroscopic data and Judd–Ofelt parameters. In addition, the emission intensity of Sr2 TiSi2 O8 :Eu 3+ is extremely sensitive to temperature. The relative sensitivity of Sr2 TiSi2 O8 :Eu 3+ is 1.1% k -1 @300 k, which is comparable to other Eu 3+ -activated temperature sensing materials. The possible mechanism of the temperature sensitive quenching characteristics was proposed. The results indicate that Sr2 TiSi2 O8 :Eu 3+ is a potential temperature sensing material.